YOU HAVE A FRIEND IN 10A - Shipstead, Maggie (London : Penguin Books, 2022)
Meet the silent cowgirl and horse wrangler escaping an ugly home life, only to fall into a decade-long triangle of unrequited love; a male novelist reckoning with his own pretentiousness as his debut novel goes to print; a honeymoon couple's time in the hills of Romania that builds into a moment of shattering tragedy. Exuding both tenderness and bite, Shipstead exposes complicated truths in this collection, sealing her reputation as a versatile master of fiction.
Contains stories that originally appeared in other publications between 2009-2017.
Keywords: Short stories